YTHDF2 is a Potential Biomarker and Associated with Immune Infiltration in Kidney Renal Clear Cell Carcinoma - Su, Ganglin; Liu, Tianshu; Han, Xiaohong; Sun, Hao; Che, Wenan; Hu, Kun; Xiao, Junwen; Li, Yanfeng; Liu, Yuchen; Li, Wujiao; Mei, Hongbing (Frontiers in Pharmacology, 2021)
Clear cell renal cell carcinoma (ccRCC or KIRC) has a high mortality rate globally. It is necessary to identify biomarkers and investigate the mechanisms those biomarkers are associated with, to improve the prognosis of patients with KIRC. N6-Methyladenosine (m6A) affects the fate of modified RNA molecules and is involved in tumor progression. Different webservers were used in our research to investigate the mRNA transcription and clinical significance of YTHDF2 in KIRC. Survival analysis revealed that patients with elevated YTHDF2 transcription had a slightly longer OS and DFS than those with low YTHDF2 expression. YTHDF2 expression was shown to be significantly associated with the abundance of immune cells such as B cells, CD8+ T cells, CD4+ T cells, macrophages, neutrophils, and dendritic cells. For a series of enrichment studies, we combined information on YTHDF2-binding molecules and expression-linked genes and identified the possible influence of “mRNA surveillance pathway,” “RNA degradation,” and “RNA transport” in the biology or pathogeny of KIRC. In addition, we identified multiple miRNA, kinase, and transcription factor targets of YTHDF2 in KIRC and constructed target networks. Overall, our findings show that YTHDF2 is a possible indicator of immune infiltration in the KIRC.